Caffeine: Towards uniformed representation and acceleration for deep convolutional neural networks - Zhang, Chen; Sun, Guangyu; Fang, Zhenman; Zhou, Peipei; Pan, Peichen; Cong, Jason (IEEE Transactions on Computer-Aided Design of Integrated Circuits and Systems, 2016)
With the recent advancement of multilayer convolutional neural networks (CNN) and fully connected networks (FCN), deep learning has achieved amazing success in many areas, especially in visual content understanding and classification. To improve the performance and energy efficiency of the computation-demanding CNN, the FPGAbased acceleration emerges as one of the most attractive alternatives. In this paper we design and implement Caffeine, a hardware/ software co-designed library to efficiently accelerate the entire CNN and FCN on FPGAs. First, we propose a uniformed convolutional matrixmultiplication representation for both computation-bound convolutional layers and communication-bound fully connected (FCN) layers. Based on this representation, we optimize the accelerator micro-architecture and maximize the underlying FPGA computing and bandwidth resource utilization based on a revised roofline model. Moreover, we design an automation flow to directly compile high-level network definitions to the final FPGA accelerator. As a case study, we integrate Caffeine into the industry-standard software deep learning framework Caffe. We evaluate Caffeine and its integration with Caffe by implementing VGG16 and AlexNet networks on multiple FPGA platforms. Caffeine achieves a peak performance of 1,460 GOPS on a medium-sized Xilinx KU060 FPGA board; to our knowledge, this is the best published result. It achieves more than 100x speed-up on FCN layers over prior FPGA accelerators. An end-to-end evaluation with Caffe integration shows up to 29x and 150x performance and energy gains over Caffe on a 12-core Xeon server, and 5.7x better energy efficiency over the GPU implementation. Performance projections for a system with a high-end FPGA (Virtex7 690t) show even higher gains.